Belarus Country Economic Memorandum : Eeconomic Transformation for Growth - World Bank (Washington, DC, 2013)
The last decade in Belarus was marked by an average economic growth rate of close to 8 percent annually and an impressive eight-fold reduction in poverty. Economic growth was initially driven by external factors, but after 2005 expansionary domestic demand became the prevalent contributor to growth. Growth was backed by large state support to the economy, sizeable public investments, and huge expansion of credit, particularly under government directed lending programs. Simultaneously, the external balance shifted from a surplus of 1.4 percent of growth development product (GDP) in 2005 to a deficit of 15.0 percent of GDP in 2010. Throughout the period 2001-10, the economic model relied on underpriced energy resources from Russia, with an annual average size of the imputed subsidy of over 13 percent of GDP. However, the existing growth model has reached its limits and cannot ensure growth sustainability without structural reforms. Going forward, the growth model will have to rely on significant productivity gains driven by structural reforms in an environment of macroeconomic stability. Macroeconomic adjustment which effectively combats the sources of external imbalances in Belarus is a critical and necessary, but insufficient condition for achieving sustainable economic growth in the medium term. The Belarusian economy is facing formidable challenges beyond the macroeconomic issue of adequately financing its external imbalances: (1) how to reallocate labor and capital to high productivity segments of the economy; (2) how to restructure the state-owned enterprise sector; and (3) how to support the underdeveloped private sector and the services sector. By successfully overcoming these challenges, Belarus will revive its competitive segments of the economy and discover untapped opportunities for growth. It will also diminish its economic dependence on underpriced energy from Russia and move up the value chain in global integration. With valuable geographical location and an educated and disciplined labor force, Belarus can restructure its economy, diversify its exports, and increase the prosperity of its people.